Sarcocornia perennis: A Salt Substitute in Savory Snacks - Clavel-Coibrié, Elsa (2021)
Salt is the primary source of sodium in the human diet, and it is associated with hypertension and increased risk of heart disease and stroke. A growing interest in halophyte plants and food products containing this type of ingredient have been observed, to reduce the NaCl daily intake. In the present work, Sarcocornia perennis was incorporated as a food ingredient into crackers to replace the salt (NaCl) and to evaluate its impact on physical properties, water activity, nutritional composition, mineral profile, total phenolic compounds, antioxidant activity, and sensory evaluation. Concentrations of powder dried S. perennis from 1 to 10% were tested by replacing the initial salt content and adjusting the flour incorporation to the initial formulation. The incorporation of S. perennis had no relevant impact on cracker firmness, but it induced an increase in their crispness. Furthermore, the incorporation of this halophyte originated darker crackers, which was revealed by a decrease of L* and an increase of b* values. In terms of nutritional composition, the incorporation of S. perennis leads to the improvement of the snack's nutritional profile, namely in terms of phenolic compounds, antioxidant activity, and minerals, highlighting the high content in potassium, magnesium, and phosphor. Crackers with a content of 5% of S. perennis were sensorily well accepted and this level should be considered the limit of incorporation accepted by the panelists. However, by substituting 1% NaCl for an equal amount of S. perennis, it is possible to obtain a 70% reduction in sodium content, which is an important contribution to reducing the overall salt content of the diet.